Is Green Technological Innovation Promoted? Policy Effect of Green Finance Reform Innovation Pilot Zones - Zhang, Shikun; Yang, Bo; Li , Yaru; Chen, Chunchun (Transformations In Business & Economics, 2025)
The implementation effect of green financial policies has always been widely concerned by scholars, and abundant research results have been achieved. However, systematic research is lacking on whether green financial policies can promote green technological innovation of enterprises and what mechanism exists at the micro level. To clarify the relationship between green financial policies and enterprises’ green technological innovation, the Green Finance Reform Innovation Pilot Zones (GFRIZs) in China were utilized as a quasi-natural experiment. Drawing on the innovation-driven theory, resource-based theory, and environmental regulation theory, the influencing effect and mechanisms of GFRIZs on enterprises’ green technological innovation were systematically investigated using the annual data from Chinese A-share listed companies from 2012 to 2023, and a multiperiod difference-in-differences method. Results show that GFRIZs can significantly promote enterprises’ green technological innovation, which is mainly achieved by relaxing financing constraints and strengthening environmental regulations. However, this effect is heterogeneous due to the differences in property rights, industry types, and pollution levels of enterprises. The conclusion provides theoretical support and empirical evidence for the government to scientifically evaluate the policy effect of GFRIZs. It also helps the government improve enterprises' green technological innovation ability by enhancing the green financial policy system, reducing the financing constraints on enterprises, and giving full play to environmental regulations.